A Novel Efficient L-Lysine Exporter Identified by Functional Metagenomics - Malla, Sailesh; van der Helm, Eric; Darbani, Behrooz; Wieschalka, Stefan; Förster, Jochen; Borodina, Irina; Sommer, Morten Otto Alexander (Frontiers in Microbiology, 2022)
Lack of active export system often limits the industrial bio-based production processes accumulating the intracellular product and hence complexing the purification steps. L-lysine, an essential amino acid, is produced biologically in quantities exceeding two million tons per year; yet, L-lysine production is challenged by efficient export system at high titres during fermentation. To address this issue, new exporter candidates for efficient efflux of L-lysine are needed. Using metagenomic functional selection, we identified 58 genes encoded on 28 unique metagenomic fragments from cow gut microbiome library that improved L-lysine tolerance. These genes include a novel L-lysine transporter, belonging to a previously uncharacterized EamA superfamily, which is further in vivo characterized as L-lysine exporter using Xenopus oocyte expression system as well as Escherichia coli host. This novel exporter improved L-lysine tolerance in E. coli by 40% and enhanced yield, titer and the specific production of L-lysine in an industrial Corynebacterium glutamicum strain by 7.8%, 9.5% and 12%, respectively. Our approach allows the sequence-independent discovery of novel exporters and can be deployed to increase titres and productivity of toxicity-limited bioprocesses.